Seismic anisotropy indicates ridge‐parallel asthenospheric flow beneath the Eastern Lau Spreading Center. Issue 2 (7th February 2015) - Menke, William; Zha, Yang; Webb, Spahr C.; Blackman, Donna K.
Abstract Seismic anisotropy beneath the Eastern Lau Spreading Center (ELSC) is investigated using both Rayleigh waves and shear waves, using data from the 2009–2010 ELSC ocean bottom seismograph experiment. Phase velocities of Rayleigh waves determined by ambient noise cross correlation are inverted for azimuthally anisotropic phase velocity maps. Splitting of S waves from five intermediate and deep focus earthquakes was determined by waveform analysis. Taken together, Rayleigh wave and S wave data indicate that significant (~2%) anisotropy extends to at least 300 km depth. Both data sets indicate a fast direction aligned within a few degrees of the N10°E striking ELSC and somewhat oblique to the N25°E strike of the neighboring volcanic arc. We therefore describe the fast direction as spreading perpendicular, not convergence perpendicular and interpret it as due to ridge‐parallel flow of the asthenosphere. However, the region arcward (east) of the ELSC has the stronger anisotropy, suggesting that the strongest flow gradients may occur in the region between the spreading center and the arc, in contrast to being centered beneath the ELSC. Fluids released from the underlying plate may produce anisotropic hydrous materials, but more importantly lower the viscosity, thus enhancing along‐strike flow. Both could contribute to an along‐strike fast direction signature. Seafloor spreading diminishes south of the seismic array, ceasing altogether south of latitude 25°S (500 km south of the array center), a region dominated by much slower tectonic extension, suggesting that asthenosphere is inflowing from the north to accommodate the increase in asthenospheric volume associated with the seafloor spreading.